2018
DOI: 10.1167/iovs.17-22930
|View full text |Cite
|
Sign up to set email alerts
|

Retinothalamic White Matter Abnormalities in Amblyopia

Abstract: PURPOSE. Amblyopia is associated with a broad array of perceptual and neural abnormalities in the visual system, particularly in untreated or unsuccessfully treated populations. Traditionally, it has been believed that the neural abnormalities are confined to the visual cortex and subcortex (e.g., lateral geniculate nucleus). Here, we investigate the presence of neuroanatomical abnormalities earlier in the visual stream, in the optic nerves and tracts, of participants with two predominant forms of amblyopia.ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 38 publications
(41 reference statements)
3
46
0
Order By: Relevance
“…For example, the human white matter is affected during normal aging as well as in age-related diseases, such as Alzheimer's or progressive cognitive degeneration (Mayda et al 2010;Wang et al 2010Wang et al , 2012Yeatman et al 2014; Thomason and Thompson 2011). The visual white matter pathways have been also shown to be affected by visual and eye disease, for example, developmental prosopagnosia (Gomez et al 2015;Thomas et al 2008), amblyopia (Allen et al 2015(Allen et al , 2018Duan et al 2015), and retinal ganglion cell damage (Ogawa et al 2014) have all been reported to affect properties of the human white matter, please see Ariel Rokem et al 2017;Millington et al 2014 for reviews. Evidence from in vivo studies suggest that macular degeneration also affects volume of the human primary visual cortex and the visual pathways (Prins et al 2016a, b;Hernowo et al 2014;Malania et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the human white matter is affected during normal aging as well as in age-related diseases, such as Alzheimer's or progressive cognitive degeneration (Mayda et al 2010;Wang et al 2010Wang et al , 2012Yeatman et al 2014; Thomason and Thompson 2011). The visual white matter pathways have been also shown to be affected by visual and eye disease, for example, developmental prosopagnosia (Gomez et al 2015;Thomas et al 2008), amblyopia (Allen et al 2015(Allen et al , 2018Duan et al 2015), and retinal ganglion cell damage (Ogawa et al 2014) have all been reported to affect properties of the human white matter, please see Ariel Rokem et al 2017;Millington et al 2014 for reviews. Evidence from in vivo studies suggest that macular degeneration also affects volume of the human primary visual cortex and the visual pathways (Prins et al 2016a, b;Hernowo et al 2014;Malania et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The first two methods are SD-Stream and iFOD1, within the CSD tractography framework (Tournier et al, 2004(Tournier et al, , 2007(Tournier et al, , 2012 . We chose the CSD framework because it has been widely used in cranial nerve studies (Allen et al, 2018;Attyé et al, 2018;Hales et al, 2018;Haykal et al, 2019;Miller et al, 2019;Puzniak et al, 2019;Schmidt et al, 2018;Xie et al, 2020a) . In brief, in the CSD-based tractography framework, fiber tracking works by stepping along a particular direction at each tracking step, with a constraint on the angle between successive steps.…”
Section: Four Compared Tractography Methodsmentioning
confidence: 99%
“…Y. Takemura et al, 2017) ON and OT (de Blank et al, 2013) RGVP (Altıntaş et al, 2017;Hofer et al, 2010) DTI (probabilistic) ON (Zolal et al, 2017) OT (Backner et al, 2018;Frezzotti et al, 2016;Glick-Shames et al, 2019;Hoffmann et al, 2012;Levin et al, 2010;Malania et al, 2017;Maleki et al, 2012;Ogawa et al, 2014;Noa Raz et al, 2015;Noa Raz & Levin, 2014;H. Takemura et al, 2019) ON and OT (Wu et al, 2019) RGVP (Ather et al, 2019) CSD (deterministic) OT (Hofstetter et al, 2019) CSD (probabilistic) ON (Attyé et al, 2018;Miller et al, 2019) OC (Puzniak et al, 2019) OT (Haykal et al, 2019;Kammen et al, 2016;Rutland et al, 2019) ON and OT (Allen et al, 2018;Hales et al, 2018) ON and OC GQI (deterministic) ON (Ho et al, 2019) OT (Burton et al, 2018;Jin et al, 2019;Matsuo et al, 2018) RGVP (Panesar et al, 2019;Yoshino et al, 2016) Abbreviations: ON -optic nerve, OC -optic chiasm, OT -optic tract.…”
Section: Dti (Deterministic)mentioning
confidence: 99%
“…In agreement with the non-human animal literature, a range of neuroanatomical changes have been reported within the visual pathway of humans with amblyopia. These include disrupted white matter structure (Allen, Schmitt, Kushner & Rokers, 2018, Allen, Spiegel, Thompson, Pestilli & Rokers, 2015, Duan, Norcia, Yeatman & Mezer, 2015, Li, Jiang, Guo, Li, Cai & Yin, 2013, Qi, Mu, Cui, Li, Shi, Liu, Xu, Zhang, Yang & Yin, 2016, Zhai, Chen, Liu, Zhao, Zhang, Luo & Gao, 2013, reduced subcortical and cortical grey matter density (Mendola, Conner, Roy, Chan, Schwartz, Odom & Kwong, 2005, and alterations in effective (Li, Mullen, Thompson & Hess, 2011) and resting state connectivity (Ding, Liu, Yan, Lin & Jiang, 2013, Liang, Xie, Yang, Yin, Wang, Yu, He & Wang, 2017, Mendola, Lam, Rosenstein, Lewis & Shmuel, 2018, Wang, Li, Guo, Peng, Li, Qin & Yu, 2014. However, it is unclear whether these changes are due to lost binocular visual input per se or because of mismatched, competing inputs from the two eyes during visual development.…”
Section: Introductionmentioning
confidence: 99%